Knowledge Management and Conceptual Modelling Towards Better Business Results - Bogdan Okreša urić; Mirko Maleković (Proceedings of the ENTRENOVA - ENTerprise REsearch InNOVAtion Conference, Split, Croatia, 6-8 September 2018, 2018)
A short review on the idea of a synergy of knowledge management and conceptual modelling methods is given in this paper. Innovative systems fostering knowledge management in modern businesses are necessary for safe and efficient knowledge management and are a welcome addition to slowly changing business models in a turbulent socio-economic environment of the modern world. The goal of this paper is to present a short discussion on various methods of knowledge management and how they are related to conceptual modelling. Furthermore, motivation for using conceptual modelling in knowledge management is argued using various references to already published research. The reasoning is steered towards the conclusions in favour of conceptual modelling in knowledge management, but not without providing strong arguments both in favour and against the starting presumption of usefulness of conceptual modelling in knowledge management.
Keywords: D83; 330; conceptual modelling; knowledge management; databases; organisational knowledge; metamodel